2022
DOI: 10.3390/agronomy12112759
|View full text |Cite
|
Sign up to set email alerts
|

Green Remediation Technology for Total Petroleum Hydrocarbon-Contaminated Soil

Abstract: In order to improve the bioremediation efficiency of petroleum-contaminated soil, five test groups were selected in this study, including native bacteria, Acinetobacter venetianus, Vetiveria zizanioides L., and Vetiveria zizanioides L. combined with Acinetobacter venetianus and biochar to compare the degradation efficiency of petroleum-contaminated soil. The results of the study showed that after a six-month bioremediation, there was no significant difference between the native bacteria and the A.V. bacteria g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Therefore, breeding transgenic, hyperaccumulative plants encoding for POP-degrading enzymes may foster certain potential in the phytoremediation of these pollutants. The adverse impact of DO and P on the biomass of aerial parts of Zea mays in the present study was weaker in sandy loam (SL) than in loamy sand (LS), probably due to the stronger binding of petroleum-derived hydrocarbons with soil particles in SL than in LS and, consequently, due to their lower bioavailability [ 107 ]. The analyzed sorbents were more effective in mitigating the adverse effects of DO than P on Zea mays , which was due to the less toxic effects of P than DO on this crop.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, breeding transgenic, hyperaccumulative plants encoding for POP-degrading enzymes may foster certain potential in the phytoremediation of these pollutants. The adverse impact of DO and P on the biomass of aerial parts of Zea mays in the present study was weaker in sandy loam (SL) than in loamy sand (LS), probably due to the stronger binding of petroleum-derived hydrocarbons with soil particles in SL than in LS and, consequently, due to their lower bioavailability [ 107 ]. The analyzed sorbents were more effective in mitigating the adverse effects of DO than P on Zea mays , which was due to the less toxic effects of P than DO on this crop.…”
Section: Discussionmentioning
confidence: 98%
“…Native plants are preferred in this case, as they easily adapt to the local climate conditions, thereby increasing the chances for successive phytoremediation [ 105 ]. The plants intended for phytoremediation should have a well-developed root system [ 18 , 27 ], e.g., those from the Poaceae family [ 21 , 27 , 30 , 106 , 107 , 108 ] used for the phytoremediation of soils polluted with petroleum-derived hydrocarbons. This plant family also includes Zea mays , used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The bio-stimulation of soil microorganisms with nutrients N and P, humidity and aeration increased the decomposition of hydrocarbons and fostered the bioremediation of the drill cuttings [56]. Lin et al (2022) [57] found that the soil pH and conductivity increased during the bioremediation experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In order to enhance the bioremediation efficiency of petroleum-contaminated soil, Lin et al (2022) selected five test groups for comparison in this study, including native bacteria, Acinetobacter venetianus (A.V. ), Vetiveria zizanioides L., and combinations of Vetiveria zizanioides L. with Acinetobacter venetianus and biochar (Figure 3B) [16]. The results showed that after six months of bioremediation, there was no significant difference in the removal efficiency of total petroleum hydrocarbons (TPH) between the native bacteria group and the A.V.…”
Section: Green Remediation Technology For Total Petroleum Hydrocarbon...mentioning
confidence: 99%